POLA KEMITRAAN NON GOVERNMENT ORGANIZATION (NGO) YAYASAN SAYAP IBU DENGAN PEMERINTAH PROVINSI DKI JAKARTA DALAM MENGATASI ANAK HOMELESS - FERNANDYA, RA SITI SASKIA; Astuti, Puji (Journal of Politic and Government Studies, 2019)
Non Government Organizations (NGOs) or Community Social Institutions (NGOs) have an important role in the social life of the community. The role is proven by the existence of social conflicts that are resolved / handled by NGOs. Like one example in the DKI Jakarta Province there is the NGO Yayasan Sayap Ibu that handles neglected / homeless children. In this study, the authors considered the NGO Yayasan Sayap Ibu unable to handle homeless children in a personal organization, therefore the presence of the government which also has an obligation to handle homeless children is an opportunity so that these two institutions can conduct partnerships. In this study, the authors used qualitative research methods. The author uses this method because the theme of this research can only be obtained by direct opinions from the empirical experience and the ability / authority of the informants in overcoming the problem of homeless children in the DKI Jakarta Province.Â Â The results of this study show about handling homeless children from partnerships between the two institutions. Sayap Ibu Foundation partnered with the DKI Jakarta Provincial Government since 1976 during the time of Governor Ali Sadikin. The results of the partnership at that time took the form of the legality of the Sayap Ibu Foundation to open up opportunities for child adoption to the community. Up to now developments (in 2019) partnerships have developed in a wider scope that aims to deal with the problem of homeless children. Policy recommendations from the results of this study to relevant stakeholders are the definitive legal basis for neglected / homeless children, because neglected children do not have meaning by definition or categorization in legal regulations. The government must place equal partnerships with the Sayap Ibu Foundation (not hierarchical relations) so that demands can be balanced and partnerships will have results in accordance with mutualism agreements.Keywords: Partnership, Sayap Ibu Foundation, DKI Jakarta Provincial Government, Homeless ChildrenÂ